2017
DOI: 10.3904/kjim.2015.149
|View full text |Cite
|
Sign up to set email alerts
|

Identification of distinctive clinical significance in hospitalized patients with endoscopic duodenal mucosal lesions

Abstract: Background/AimsDuodenitis is not infrequent finding in patient undergoing endoscopy. However, hospitalized patients have a higher incidence of secondary duodenal mucosal lesions that might be related with inflammatory bowel disease (IBD), cytomegalovirus (CMV) infection, tuberculosis, immunologic disorders, or other rare infections. We aimed to identify clinicopathologic features of duodenal mucosal lesions in hospitalized patients.MethodsAll hospitalized patients having duodenal mucosal lesions were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
6
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 33 publications
2
6
1
1
Order By: Relevance
“…[ 3 ] Non- H. pylori and non-NSAID duodenal ulcers are reportedly associated with multiple ulcers; in contrast, H. pylori -related ulcers usually occur singly [ 9 ]. This result is similar to the finding of Han et al [ 5 ].…”
supporting
confidence: 93%
See 4 more Smart Citations
“…[ 3 ] Non- H. pylori and non-NSAID duodenal ulcers are reportedly associated with multiple ulcers; in contrast, H. pylori -related ulcers usually occur singly [ 9 ]. This result is similar to the finding of Han et al [ 5 ].…”
supporting
confidence: 93%
“…In previous studies, NSAIDs were found to affect the duodenal mucosa in only 13% of patients with H. pylori -negative duodenal ulcers [ 11 ], and histologic changes in the duodenum were negligible [ 12 ]. These results may explain the findings of Han et al [ 5 ].…”
supporting
confidence: 84%
See 3 more Smart Citations